Multimodality imaging in endomyocardial fibrosis: An unusual etiology of heart failure (2021)
Endomyocardial fibrosis (EMF) is a condition that was first reported in 1948 in Africa, and its geographical distribution is strongly related to socioeconomic, cultural, and environmental status. More than half of the cases are reported in countries in sub-Saharan Africa; however, this condition has been described in various parts of the world. The associated factors have been previously described and include malnutrition, parasitic infection, noninfectious systemic diseases, and genetic conditions. The presence of fibrotic thickening of the endocardium secondary to inflammation generates functional alterations, which are detected by noninvasive methods such as echocardiography, with characteristic findings of a restrictive syndrome and an alteration of the ventricular chamber in the presence of dilated atria. We describe the case of a patient with decompensated heart failure and imaging findings consistent with EMF.